Integration of Non‐market and Market Activities in Cross‐border Mergers and Acquisitions. (10th November 2017) - Ahammad, Mohammad F.; Tarba, Shlomo Y.; Frynas, Jedrzej George; Scola, Andrew
Abstract: Drawing on resource dependence theory and the resource‐based view, we investigate the interactions between market and non‐market activities of firms in the context of the post‐merger integration phase in cross‐border mergers and acquisitions (M&As). Based on a cross‐country survey of 111 M&A practitioners who were personally involved in cross‐border M&As around the world, we test seven hypotheses on various market and non‐market aspects of post‐merger integration. We find a positive correlation between buffering strategies and adaptive capabilities in the non‐market environment and between bridging and adaptive capabilities in the market environment. However, we could not find any significant correlation between buffering and adaptive capabilities in the market environment and bridging and adaptive capabilities in the non‐market environment. We also find that adaptability in the non‐market environment is positively correlated with adaptability in the market environment, and in turn adaptability in the market environment leads to positive organizational performance of a cross‐border M&A. These results provide further support for the value of the alignment between market and non‐market activities and help to fill a gap in the literature on the market−non‐market interactions in post‐merger integration.